Resource Productivity in Milk Production on Mixed Dryland Farms in Nagaur District (RAJ.) - Vyas, D L (Annals of Arid Zone, 2016)
Resource productivity of dairy cows on dryland farms in Nagaur district ofarid western Rajasthan was examined for 1977-78 to 1979-80. Fixed cost and labour required subtractive corrective measures togetherwith appropriate increases in feeds and fodder to improve the milk productivity on mixed dryland farms.